Efektivitas Dan Kelengkapan Bangunan Sabo Di Sungai Togurara Daerah Gunungapi Gamalama - Ardian Alfianto; Jati Iswardoyo; cosmas bambang sukatja (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2019)
The lahar flow that occurred after the 2012 Gamalama Volcano eruption, leading to the eastern valley flowing downstream through the Togurara River to the center of Ternate City and Sultan Babullah Airport. To overcome the potential of lahar flow in the river since 2013 - 2016, several sabo dams and building facilities have been built. Based on the results of the calculation of deposits that potentially become lahar flows in 2016, the built-in capacity of the Sabodam has not been able to control the volume of sediment in the upstream of the river, then in the year 2017, 2018 constructed several additional Sabodam. In order to determine the effectiveness, feasibility and conditions of the completeness of Sabodam, is done field assessment on 25 27 September 2018, the method used was a mathematical approach based on sabo technology. The assessment was in the form of a field survey, simple measurements, interviews with the Sabodam management agency and local residents related to the lahar flow that had occurred. With the capacity of several additional Sabodams built in series, the average river bed slope was originally 9.09% to 6.83%. After the construction of Sabodam, the maximum lahar flow was once as high as 7 m, but now it decreases do 4.2 m. As the slope of the Togurara River slopes progressively, the lahar flow rate and its destructive power are reduced, so that Ternate City and Sultan Babullah Airport are spared from lahar disaster.Keywords: Lahar flow, sabodam, sabo technology, slope of riverbed, Togurara River.